Effects of cerclage suture type on pregnancy and neonatal results: Mersilene suture &prolene suture (Annals of Medical Research, 2022)
Aim: The aim of this study is to compare pregnancy and neonatal results with regards to the thickness of the suture material used in the transvaginal cerclage operation.Materials and Methods: Patients who were subject to transvaginal cervical cerclage due to cervical insufficiency were evaluated in a secondary care center between 2103 and 2021 retrospectively. The demographic data, cerclage indications (ultrasound induced, prophylactic, or physical examination induced),  number of pregnancy weeks at cerclage, type of cerclage suture (prolene, mersilene), type of cerclage (McDonald, Shirodkar), total pregnancy weeks, delivery method (cesarean (C/S), normal spontaneous vaginal delivery) of each patient were recorded.  Additionally, birth weight, 1st and 5th minute APGAR scores, and neonatal intensive care unit (NICU) requirements were recorded as neonatal parameters. Patients were divided into two groups with regard to the type of cerclage suture (mersilene or prolene) and maternal, neonatal and pregnancy results were compared between these groups.Results: The study included 151 patients in total. Prolene sutures were used for 69 of the patients (45.7%) and mersilene sutures for 82 patients (54.3%) Cerclage was applied for 18 patients (11.9%) depending on the ultrasound findings, 121 patients (80.1%) depending on emergency and 12 patients (7.9%) depending on history. Gravida increased significantly in the prolene suture group (p=0.021). Pregnancy week was found to be significantly lower in the mersilene suture group [32.5 w (15-40)] compared to the prolene suture group [37.0 w (15-41)] [37.0 w (15-41)](p
Keywords: Cerclage suture; Preterm birth prevention; Short cervical length; Mersilene; Monofilament